Does corporate financial performance promote ESG: Evidence from US firms - Khalfaoui Hamdi; Hassan Guenich; Moufida Ben Saada (Cogent Business & Management, 2022)
Studying Corporate Environmental, Social and Governance responsibility (ESG) and its consequences remain a topical concern of the company's stakeholders including governmental and non-governmental organizations, investors and researchers over the past few decades. While most research has studied and validated the beneficial effect of ESG on financial performance. The few studies that have explored the nexus between financial performance and ESG relationship are conducted in a double causality framework. Thus, this research fills this gap by studying the effect of financial performance on ESG. Using a random-effects panel data model for more than 10,000 firm-year observations of 504~U.S. firms during the period 2000-2020, the results show a positive relationship between financial performance and ESG. Furthermore, cash holding, minority interest and inflation have significantly the expected sign. Yet, the market-to-book value seems insignificant. Interestingly, during periods of high economic policy uncertainty, oil price uncertainty and leverage, the impact of companies' financial performance on ESG decreases differently according to the three components of the ESG. These findings are robust and consistent with alternative econometric specifications and alternative measures of dependent variable and control variables.
Keywords: 650; ESG performance; Corporate Financial Performance; Economic Policy Uncertainty; Leverage; Oil Price Uncertainty; US firms